A Variable-Parameter Model of Exporting Behaviour - Batchelor, R. A. (Review of Economic Studies, 1977)
Journal Article A Variable-Parameter Model of Exporting Behaviour Get access R. A. Batchelor R. A. Batchelor National Institute of Economic and Social Research Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 1, February 1977, Pages 43–57, https://doi.org/10.2307/2296972 Published: 01 February 1977 Article history Received: 01 October 1975 Accepted: 01 May 1976 Published: 01 February 1977